(untitled) (Research, Society and Development, 2023)
The study of watersheds is essential to understand the hydrological processes that occur in these environments, as well as serve as a basis for a better management of water resources. This study aimed to carry out the physiographic characterization of the Treze de Maio river basin (BHTM) using the geoprocessing software QGIS 3.18.1 and SAGA, together with the Google Earth Engine (GEE) platform, through the Digital Terrain Model, from in order to promote information aimed at assisting in the management of water resources and in the management of agricultural activities in the region. In this study, physiographic variables were analyzed, 13 of which were secondary and 10 generated with the support of Geographic Information System and electronic spreadsheet. BHTM had a total area of ​​110.6 km², a perimeter of 105 km and a main axis length of 26.1 km, thus presenting a medium drainage network, with long channels and without many branches. Furthermore, it presented a 4th order fluvial hierarchy along with altitudes ranging from 185.4 m to 285 m. It was concluded that BHTM does not present characteristics of susceptibility to floods. As for the use and occupation of the soil, there was a constant reduction of forest formation in the years studied and, as a counterpoint, a significant increase in the areas occupied by pasture.